STRUKTUR ANATOMI DAN IDENTIFIKASI DELAPAN JENIS KAYU PERDAGANGAN DARI KEBUN PERCOBAAN DI JAWA BARAT - Sri Rulliaty M (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Eight wood species from forest experimental garden in West Java were observed for identification purposes. All wood species could be identified one from the others, due to their distinguished conspicuous characters. Kecapi (Sandoricum kucape Merr.) on the other hand, showed characters that matched only the previous description of the genus. Such characters, were apparently not sufficed to describe the species.